2018
DOI: 10.4103/aer.aer_177_17
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure changes during laparoscopic surgery in Trendelenburg position in patients anesthetized with propofol-based total intravenous anesthesia compared to sevoflurane anesthesia: A comparative study

Abstract: Background:Intraocular pressure (IOP) is increased during laparoscopic surgery with Trendelenburg position and may contribute to deleterious effects on optic nerve in susceptible patients.Aims:The primary objective of this study is to compare the effects of propofol-based total intravenous anesthesia (TIVA) with those of sevoflurane anesthesia on IOP in patients undergoing lower abdominal laparoscopic surgery in Trendelenburg position. Secondary objectives are to compare hemodynamic changes, mean arterial pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Previous studies compared propofol-based total intravenous anesthesia (TIVA) to sevoflurane anesthesia using IOP measurement. Kaur et al [ 10 ] demonstrated that propofol-based TIVA was superior to sevoflurane anesthesia by direct intraoperative measurement of IOP during laparoscopic surgery in the Trendelenburg position. Yoo et al [ 11 ] also observed that propofol-based TIVA is superior to sevoflurane anesthesia in attenuating the increase of IOP during laparoscopic surgery in the Trendelenburg position.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies compared propofol-based total intravenous anesthesia (TIVA) to sevoflurane anesthesia using IOP measurement. Kaur et al [ 10 ] demonstrated that propofol-based TIVA was superior to sevoflurane anesthesia by direct intraoperative measurement of IOP during laparoscopic surgery in the Trendelenburg position. Yoo et al [ 11 ] also observed that propofol-based TIVA is superior to sevoflurane anesthesia in attenuating the increase of IOP during laparoscopic surgery in the Trendelenburg position.…”
Section: Introductionmentioning
confidence: 99%
“… 50 , 51 , 52 , 53 Nonetheless, some anesthetic medications, in particular, propofol, have been reported to mitigate an increased IOP and its sequelae during surgery even in the presence of an increased IAP and steep patient positioning. 54 , 55 , 56 , 57 , 58 …”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53] Nonetheless, some anesthetic medications, in particular, propofol, have been reported to mitigate an increased IOP and its sequelae during surgery even in the presence of an increased IAP and steep patient positioning. [54][55][56][57][58] Controversy It has been claimed that all of the cranial sinuses lie in the "interperiosteodural space." 14,15 Although some general features characterize the periosteal and meningeal dural layers, the border between them is not distinct.…”
Section: Pressure Transductionmentioning
confidence: 99%
“…Furthermore, our anesthesia technique was not standardized during this study. Recent studies reported that TIVA was more effective than inhalational anesthesia with sevoflurane in controlling IOP changes during TP . Therefore, anesthesia technique should ideally be standardized in all patients, although this is not realistic in a larger cohort study involving multiple anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that TIVA was more effective than inhalational anesthesia with sevoflurane in controlling IOP changes during TP. 23,24 Therefore, anesthesia technique should ideally be standardized in all patients, although this is not realistic in a larger cohort study involving multiple anesthesiologists. Regarding the ophthalmic examination, the visual field test is based on a subjective examination and the corresponding fluctuation should be considered as an important context, because most patients were not accustomed to the visual field test.…”
Section: Discussionmentioning
confidence: 99%